Hubungan Dimensi Kualitas Pelayanan Kesehatan Dengan Kepuasan Pengguna BPJS-Kesehatan Penerima Bantuan Iuran (PBI) di Kota Denpasar - Hutahayan, Nelly Srimaya; Arjawa, I Gusti Putu Bagus Suka; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study was conducted with the aim of determining the relationship between service quality dimensions and the satisfaction of BPJS-Kesehatan Contribution Assistance Recipients (PBI) users in Denpasar City. This study uses an explanatory quantitative method. The number of samples in this study was 100 respondents, which were determined using the Slovin formula with a Margin of Error of 10%. The respondents in this study were BPJS-Health Beneficiary Contribution Assistance (PBI) card users in Denpasar City. The sample determination used the Simple Random Sampling technique. Data collection techniques by distributing questionnaires to respondents. In proving and analyzing this, validity and reliability tests, multiple linear regression tests, classical assumption tests and hypothesis tests were used.             The test results show that: 1) Partially (t-test), all dimensions of service quality have a positive and significant relationship with the satisfaction of BPJS-Health Beneficiary Contribution Assistance (PBI) users in Denpasar City. The Physical Evidence Dimension ( ) has a regression coefficient of 6.165 > 1.661, Reliability ( ) has a regression coefficient of 3.859 > 1.661, Responsiveness ( )  has a regression coefficient of 9.136 > 1.661, Assurance ( ) has a regression coefficient of 12.775 > 1.661, Empathy ( ) has a regression coefficient of 16.592 > 1.661, with each significance value < 0.05. This test uses a Margin Of Error of 5% so that it gets a t-value of 1.661. 2) Simultaneously (f test), a significance value of 0.000 < 0.05 was obtained, which means that all independent variables together have a significant relationship with the satisfaction of BPJS-Health Users Receiving Contribution Assistance (PBI) in Denpasar City.